Activated carbon immersed in water—the origin of linearcorrelation between enthalpy of immersion and oxygencontent studied by molecular dynamics simulation - Terzyk, A.; Gauden, P.; Furmaniak, S.; Wesolowski, R.; Kowalczyk, Piotr (Royal Society of Chemistry, 2010)
First Molecular Dynamics simulation results of activated carbon immersion in water are reported. Using a Virtual Porous Carbon Model of ‘‘soft’’ carbon the influence of surface oxygen content, distribution of groups and micropore diameter on the enthalpy of immersion is studied. The empirical relation between enthalpy and concentration of surface groups (as well as polar surface area) is reproduced by molecular simulation results. It is shown that for strongly hydrophobic carbons immersed in water, the water–vapour interface inside pores appears. This interface vanishes with the rise in content of surface oxygen. We discuss some nuances of the interfacial region using proximal distribution functions and hydrogen bonds statistics. Finally we conclude that the mechanism of immersion process is in accordance with Pratt–Chandler theory of hydrophobic interactions.